A Walk to Remember - Sparks, Nicholas (London Sphere, 2007)
This is a story of the love that grew between Landon and Jamie - Jamie was reluctant at first, to allow herself to develop a relationship with Landon - As her grew to know her better, he learned about the disease that was going to cut her life short.
Originally published: Boston, Mass.: Warner, 1999; London: Bantam, 2000.
Keywords: Children of clergy; Teenage boys